Defenders - Stonehouse, Bernard; Francis, John, 1950- (Lake Mary : Tangerine Press, 1999)
Describes the many ingenious ways different animals of land, sea, and air defend themselves and their offspring.
Keywords: Animal defenses -- Juvenile literature; Animal defenses; Literature